2021
DOI: 10.36660/ijcs.20210181
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profile of Patients with Infective Endocarditis at three Tertiary Centers in Brazil from 2003 to 2017

Abstract: With improved resources for the prevention, diagnosis, and treatment of infective endocarditis (IE), significant changes in the characteristics of the disease have been reported over time. If, on the one hand, the prevalence of IE due to rheumatic valve disease has decreased, on the other, there has been an increase in IE related to degenerative valve disease in older adults, valve replacement surgery, the implantation of intracardiac devices, and the use of injectables and hemodialysis.Coincidentally, IE case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…The incidence rate of IE in males was, on average, 11.39/100,000 person-years; in females, it was 5.24/100,000 person-years [ 12 , 24 ]. On average, males comprised 65.8% of patients who developed IE, while females comprised only 34.2% of patients [ 12 , 14 - 19 , 21 - 23 , 26 , 27 , 29 - 31 ]. However, one study done in 2022 found that the incidence of developing IE between males and females was equal [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The incidence rate of IE in males was, on average, 11.39/100,000 person-years; in females, it was 5.24/100,000 person-years [ 12 , 24 ]. On average, males comprised 65.8% of patients who developed IE, while females comprised only 34.2% of patients [ 12 , 14 - 19 , 21 - 23 , 26 , 27 , 29 - 31 ]. However, one study done in 2022 found that the incidence of developing IE between males and females was equal [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…Along with comparing the incidence of IE between the sexes, it’s also been shown that there is a variation in the age at which each sex develops IE. Most patients with IE were between 60 and 79 years old, with an average of 62.2 years old [ 17 - 19 , 22 , 35 , 36 ]. Erichsen et al observed that the mean age of IE diagnosis in both sexes has increased steadily, but no study reports variations towards one sex [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations